The Effect of Acidic and Alkaline Seawater on the F-Actin-Dependent Ca2+ Signals Following Insemination of Immature Starfish Oocytes and Mature Eggs - Nunzia Limatola; Jong Tai Chun; Suzanne C. Schneider; Jean-Louis Schmitt; Jean-Marie Lehn; Luigia Santella (Cells, 2023)
In starfish, the addition of the hormone 1-methyladenine (1-MA) to immature oocytes (germinal vesicle, GV-stage) arrested at the prophase of the first meiotic division induces meiosis resumption (maturation), which makes the mature eggs able to respond to the sperm with a normal fertilization response. The optimal fertilizability achieved during the maturation process results from the exquisite structural reorganization of the actin cytoskeleton in the cortex and cytoplasm induced by the maturing hormone. In this report, we have investigated the influence of acidic and alkaline seawater on the structure of the cortical F-actin network of immature oocytes of the starfish (Astropecten aranciacus) and its dynamic changes upon insemination. The results have shown that the altered seawater pH strongly affected the sperm-induced Ca2+ response and the polyspermy rate. When immature starfish oocytes were stimulated with 1-MA in acidic or alkaline seawater, the maturation process displayed a strong dependency on pH in terms of the dynamic structural changes of the cortical F-actin. The resulting alteration of the actin cytoskeleton, in turn, affected the pattern of Ca2+ signals at fertilization and sperm penetration.